PROFIL PETERNAK BABI SKALA KECIL DI KELURAHAN HINEKOMBE DISTRIK SENTANI KABUPATEN JAYAPURA - Suparman; Hetharia, Lucas Filips (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
This study aims to determine the profile of the existence of small-scale pig farms in Hinekombe Village, Sentani District, Jayapura Regency. The method used in this study is a survey method with data collection techniques by observation through direct interviews with the help of a list of questions. Interviews were conducted with 15 farmers, respondents who were selected by purposive random sampling from small-scale pig farmers in Hinekombe Village, Sentani District. The data collected, processed and presented descriptively. The results showed that 60% of under 30 years old and 40% of 30-50 years old were in the category of productive age workers, the level of education of breeders was 33.33%, high school was 26.67%, junior high school was 6.67%. , SD is 13.33% while 20% for respondents who do not have education or drop out of school, experience raising 1-5 years is 40%, 6-10 years is 46.67% and >10 years 13.33% means that respondents have more experience is above 5 years, the number of dependents in the family is below 4 (<4) dependents/head of family by 93.33% of the total respondents. For the number of dependents above 5 (> 6) people/head of family by 6.67% and the respondents' reasons for raising livestock as a source of income as much as 73.33% and 26.67% stated that it was a sideline business or leisure time. From the results of this study, it can be concluded that the profile of farmers in small-scale pig rearing businesses in Hinekombe Village, Sentani District is classified as productive age workers, has good motivation with secondary education levels and has the reason that pig rearing business is a productive business to support the family economy